2017
DOI: 10.5489/cuaj.4387
|View full text |Cite
|
Sign up to set email alerts
|

Continuous antibiotic prophylaxis in the setting of prenatal hydronephrosis and vesicoureteral reflux

Abstract: Continuous antibiotic prophylaxis (CAP) has traditionally been offered for children with recurrent urinary tract infections (UTIs) or those at risk, including children diagnosed with prenatal hydronephrosis (HN) and vesicoureteral reflux (VUR). However, indications for antibiotic prophylaxis are controversial, data on who should benefit from this therapy is conflicting and, thus, guidelines are unable to provide conclusive recommendations. In the setting of prenatal HN, although randomized trials are currently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Since VUR predisposes to UTIs, daily prophylactic antibiotics are prescribed for higher grades of VUR. Although recent studies have found conflicting evidence to support this practice, most guidelines still recommend it [15,19]. The definite treatment for VUR is strictly surgical.…”
Section: Discussionmentioning
confidence: 99%
“…Since VUR predisposes to UTIs, daily prophylactic antibiotics are prescribed for higher grades of VUR. Although recent studies have found conflicting evidence to support this practice, most guidelines still recommend it [15,19]. The definite treatment for VUR is strictly surgical.…”
Section: Discussionmentioning
confidence: 99%
“…UTIs in the pediatric population are associated with long-term complications, including hypertension, renal insufficiency, renal scarring, and growth impairment [16]. Newborns with AHN have been shown to have a twelve-fold higher risk of hospitalization, predominately in the first year of life, and VUR accounts for approximately 10%-15% of children with prenatal HN [17]. Both hydroureteronephrosis and VUR are considered risk factors for febrile UTIs [14].…”
Section: Review Discussionmentioning
confidence: 99%
“…Recently, a large multicenter, randomized study including 607 children with VUR diagnosed after the first or second UTI and with a 2-year clinical follow-up demonstrated that CAP is associated with a significant reduction in the risk of UTI episodes but not new scars (Grade of Recommendation A) (58). Recent meta-analysis have demonstrated benefits of CAP in infants with all degrees of VUR (59)(60)(61)(62).…”
Section: Continuous Antibiotics Prophylaxis (Cap)mentioning
confidence: 99%